2018
DOI: 10.1155/2018/5481909
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Stereotactic Body Radiotherapy for Recurrent or Residual Hepatocellular Carcinoma after Transcatheter Arterial Chemoembolization

Abstract: Aim To evaluate the efficacy and toxicity of hypofractionated stereotactic body radiotherapy (SBRT) for patients with recurrent or residual hepatocellular carcinoma (HCC) after transcatheter arterial chemoembolization (TACE). Methods Between June 2008 and July 2015, thirty-three patients with HCC were treated by SBRT. There were 63 lesions in 33 patients. A total dose of 39–45 Gy/3–5 fractions was delivered to the 70–80% isodose line. Results Objective response rate (CR + PR) was 84.8% at 6 months. The overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The mechanism of biocompatibility can be explained from many angles. Yao et al 55 found that with the increase of the deacetylation degree, the biocompatibility would be better. The theory of the electrostatic attraction between the chitosan molecules and the cells was accepted by some researchers.…”
Section: General Properties Of Chitosanmentioning
confidence: 99%
“…The mechanism of biocompatibility can be explained from many angles. Yao et al 55 found that with the increase of the deacetylation degree, the biocompatibility would be better. The theory of the electrostatic attraction between the chitosan molecules and the cells was accepted by some researchers.…”
Section: General Properties Of Chitosanmentioning
confidence: 99%
“…In addition, two other studies were discovered from the reference lists of the selected papers and were included. Hence, 12 studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] involving 757 patients were ultimately included in our analysis; the inclusion process is summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It is to inject chemotherapy drugs directly into tumor blood supply artery through a catheter which can improve local drug concentration of tumor to increase the ability to kill cancer cells, achieve embolization of tumor blood vessels and block the blood supply of a tumor, tumor tissue necrosis, shrinkage, and disappearance. However, tumor tissues could not be eliminated through TACE [17] . There are mainly three reasons.…”
Section: Discussionmentioning
confidence: 99%